Quantitative ethnobotanical assessment of plant resources of District Swabi Khyber Pakhtunkhwa, Pakistan - Anwar, Maqsood; Akhtar, Naveed (Ethnobotany Research and Applications, 2025)
Background: Plants are essential natural resources on our planet, providing food, shelter, fuel, and medicinal constituents for humans. The Indigenous knowledge surrounding these plants is of great scientific and cultural relevance. Methods: This study was conducted in District Swabi from 2019 to 2020. Field visits and interviews were systematically arranged across the four seasons—spring, summer, autumn, and winter—at eight selected stands. A total of 45 respondents were interviewed, with the majority being elderly individuals aged 65 years and above. The interviews utilized a semi-structured questionnaire format, which included multiple questions addressing the ethnobotanical uses of plants. Relative frequency citation, use value, family use value, and direct matrix ranking were the various quantitative indices used for the assessment of the ethnobotanical data. Results: In the study area, 177 species from 47 families were identified as ethnobotanically significant plants. The results of the quantitative ethnobotanical study indicated that the relative frequency citation (RFC) values varied from 0.04 to 0.82. The use value (UV) was observed to range between 0.04 and 1.73, and the family use value (FUV) exhibited a range of 0.04 to 1.73. Additionally, the direct matrix ranking (DMR) values for 14 trees were recorded to range between 8 and 33. Conclusions: Residents of the research area rely on indigenous plants for their basic needs, such as fuel wood and fodder. However, the local flora is under threat as a result of overgrazing and improper harvesting. Effective conservation measures such as controlled grazing, reforestation, and rangeland management are required for long-term plant resource management. Keywords: Ethnobotany, Assessment, Quantitative indices, Plant resources, Indigenous plants, Indigenous knowledge, Swabi.